The selective electrochemical fluorination of S-alkyl benzothioate and its derivatives - Kuribayashi, Shunsuke; Kurioka, Tomoyuki; Inagi, Shinsuke; Lu, Ho-Jung; Uang, Biing-Jiun; Fuchigami, Toshio (Beilstein Journal of Organic Chemistry, 2018)
We herein report that the regioselective anodic fluorination of S-alkyl benzothioate and its derivatives in various aprotic solvents using Et3N·nHF (n = 3–5) and Et4NF·nHF (n = 3–5) as supporting electrolyte and a fluorine source successfully provided the corresponding α-fluorinated products in moderate yields. Dichloromethane containing Et4NF·4HF was found to be the most suitable combination as electrolytic solvent and supporting salt as well as fluorine source for the anodic fluorination. The electrochemical fluorination of cyclic benzothioates such as benzothiophenone was also achieved.
Keywords: anodic cyclization; diastereoselective fluorination; electrosynthesis; fluorobenzothiophenone; selective fluorination